From the water mirror to globalization 2.0 (2017)
What is intended in this essay is nothing more than to approximate a reflection on China yesterday and today. And, specifically, about what we know and what we are being informed now with such enthusiasm by all means, framing current developments, but also of image and thought as they have evolved over time. On the other hand, it seeks to encourage self-criticism against studies and research that are carried out in our environment and that often reflect a certain accommodation to theses and theories that are accepted with little resistance. If China is a great challenge in terms of its ability to shape the world of tomorrow, the challenge we have to adjust our analytical tools seems to be even greater. In such a way, what is wanted is to invite a calm reflection from elements that have accumulated in several centuries and that help explain some of the biases with which we try to decipher the sinic.